MENJAGA POLA MAKAN SERTA EDUKASI GIZI PADA ANAK SEKOLAH DASAR - Rizik Habibullah Nurusyaikha; Nana Hendra Cipta; Siti Rokmanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Indonesia is currently facing two different nutrition crises due to shifting nutrition. Based on the findings of nutrition screening conducted in a number of elementary schools in Cilincing Subdistrict, North Jakarta, malnutrition occurs in 28% of the population, with the prevalence of obesity being three times greater than underweight. Malnutrition can interfere with normal growth and development of children, increase the risk of disease, and increase hospital costs. After a meeting with the school, it was decided that nutrition education was needed for elementary school students as they had never received nutrition teaching before. The aim of this study was to improve knowledge about balanced nutrition among school-age children and school administrators. In SD Rorotan 03 and SD Rorotan 07, Cilincing sub-district, North Jakarta, the nutrition education was conducted in April 2018 after preparation in March 2018. "Tumpeng Gizi Balang" (TGS), "10 Messages of Balanced Nutrition," and a Santing Decline Chart" were among the education resources. The research findings show that raising primary school students' awareness of balanced nutrition can be achieved through lecture-style nutrition teaching. Education participants know the types of foods that make up the staple diet, as well as fruits, vegetables, and protein sources. Therefore, nutrition education is a successful program to improve primary school students' knowledge, attitudes and behaviours regarding balanced nutrition.